2018
DOI: 10.1038/s41557-018-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetically encoded lipid–polypeptide hybrid biomaterials that exhibit temperature-triggered hierarchical self-assembly

Abstract: Post-translational modification of proteins is a strategy widely used in biological systems. It expands the diversity of the proteome and allows for tailoring of both the function and localization of proteins within cells as well as the material properties of structural proteins and matrices. Despite their ubiquity in biology, with a few exceptions, the potential of post-translational modifications in biomaterials synthesis has remained largely untapped. As a proof of concept to demonstrate the feasibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 66 publications
1
91
0
Order By: Relevance
“…Knowledge of the LLPS behavior of proteins as af unction of all thermodynamic variables, including pressure, is of directr elevance to recent efforts to designp roteinlike heteropolymer sequences with novel materials properties, including desirableL LPS behaviors. [36,[65][66][67][68][69][70]169] In ab roader technological context,s uch knowledge is also essential in areass uch as protein crystallization (LLPS occurs generally under conditions where the protein is metastablew ith respectt oc rystallization), protein purification, formulation development for therapeutic proteins (including the possibility of operating at industrial scales larger than other relatedt echniques as ultrafiltration, drying,c hromatography,a nd dialysis), and high-pressuref ood processing. [2,3,49,73,74,[196][197][198] It is hoped that the present summary of the initial yetpromising findings on pressure effects on biomolecular condensates will spur more efforts in this exciting area of interdisciplinary research.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the LLPS behavior of proteins as af unction of all thermodynamic variables, including pressure, is of directr elevance to recent efforts to designp roteinlike heteropolymer sequences with novel materials properties, including desirableL LPS behaviors. [36,[65][66][67][68][69][70]169] In ab roader technological context,s uch knowledge is also essential in areass uch as protein crystallization (LLPS occurs generally under conditions where the protein is metastablew ith respectt oc rystallization), protein purification, formulation development for therapeutic proteins (including the possibility of operating at industrial scales larger than other relatedt echniques as ultrafiltration, drying,c hromatography,a nd dialysis), and high-pressuref ood processing. [2,3,49,73,74,[196][197][198] It is hoped that the present summary of the initial yetpromising findings on pressure effects on biomolecular condensates will spur more efforts in this exciting area of interdisciplinary research.…”
Section: Discussionmentioning
confidence: 99%
“…Above T c the ELP gets further dehydrated decreasing repulsion between the coronas that drive macroscale self‐assembly (stage 3). Reproduced with permission . Copyright 2018, Springer Nature.…”
Section: Elp‐hybrid Self‐assembliesmentioning
confidence: 99%
“…The incorporation of ELRs into the composite hydrogels can be used to improve the mechanical properties of the network as well as provide a broad range of bioactive cues that promote cell adhesion and proliferation. [274][275][276][277][278][279] For instance, the combination of collagen with ELRs enables the production of biofunctional hydrogels with tunable mechanical properties for the regeneration of bone and soft tissues injuries, or for the manufacture of vascular grafts. [280][281][282][283][284] Indeed, it has been demonstrated that the osteoinductive activity of collagen can be synergistically combined with the mechanical properties of the ELRs to biofabricate 3D polymeric networks to guide tissue regeneration.…”
Section: Hybrid Elr-based Scaffoldsmentioning
confidence: 99%